2020
DOI: 10.2298/jsc191023003b
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation of groundwater contaminated with petroleum hydrocarbons applied at a site in Belgrade (Serbia)

Abstract: Due to their extensive use, petroleum hydrocarbons are among the most common groundwater contaminants. Compared to the traditional methods of physical pumping of contamination from the aquifer and subsequent treatment (e.g. pump and treat), bioremediation is an economically costeffective technology. The aim of this remediation approach is to biologically, most often by the microbiological activity, transform contaminants into nontoxic compounds. More precisely, it is an active remediation process that involves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 24 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…The results showed that the thickness of sandy-gravelly deposits in this area was in the range from several centimeters to several meters (Fig. 3; Bulatovic ´et al, 2020). It is important to note that these porous unbound sediments can facilitate transport of petroleum pollutants down to the groundwater level depths.…”
Section: Study Areamentioning
confidence: 81%
“…The results showed that the thickness of sandy-gravelly deposits in this area was in the range from several centimeters to several meters (Fig. 3; Bulatovic ´et al, 2020). It is important to note that these porous unbound sediments can facilitate transport of petroleum pollutants down to the groundwater level depths.…”
Section: Study Areamentioning
confidence: 81%
“…Groundwater pollution with petroleum hydrocarbons is usually accidental, as was the case in Nigeria [16], where oil spilled from a damaged pipeline and polluted the environment (including the groundwater). Elevated hydrocarbon concentrations have also been detected in Serbia, on the site of a district heating plant in New Belgrade [17]. In this case, a suspected environmental incident led to testing of the groundwater quality.…”
Section: Introductionmentioning
confidence: 89%